Efficacy and safety of sitagliptin as compared with glimepiride in Japanese patients with type 2 diabetes mellitus aged ≥ 60 years (START‐J trial). Issue 8 (12th April 2017) - Terauchi, Yasuo; Yamada, Yuichiro; Ishida, Hitoshi; Ohsugi, Mitsuru; Kitaoka, Masafumi; Satoh, Jo; Yabe, Daisuke; Shihara, Nobuyuki; Seino, Yutaka
Abstract : The aim of this study was to evaluate the efficacy and safety of sitagliptin administered to elderly patients with type 2 diabetes mellitus (T2DM) for 1 year as compared with glimepiride. Patients aged ≥60 years with T2DM and inadequately controlled blood glucose were randomly assigned to sitagliptin 50 mg once daily or glimepiride 0.5 mg once daily for 52 weeks. The primary efficacy endpoint was the change in glycated haemoglobin (HbA1c) from baseline to week 52. Secondary efficacy endpoints included self‐monitored blood glucose and weight. Safety endpoints were adverse events including hypoglycaemia. Administration of sitagliptin or glimepiride to elderly patients with T2DM resulted in a significant decrease in HbA1c change from baseline. At 52 weeks, the least squares mean difference between the treatments was 0.11% (95% confidence interval [CI] −0.02 to 0.24; P = .087) (1.2 mmol/mol [−0.2 to 2.6]). The upper limit of the CI was below the predefined non‐inferiority margin (0.3% [3.3 mmol/mol]), demonstrating non‐inferiority of sitagliptin to glimepiride for the primary endpoint. Sitagliptin resulted in a significantly lower incidence rate of non‐serious hypoglycaemia than glimepiride during the 52 weeks (4.7% vs 16.1%; P = .002); thus, sitagliptin is a useful therapeutic option for elderly patients with T2DM.